2D MXenes for Electromagnetic Shielding: A Review. (22nd April 2020) - Iqbal, Aamir; Sambyal, Pradeep; Koo, Chong Min
Abstract: Since the first report on electromagnetic interference (EMI) shielding of 2D Ti3 C2 T x in 2016, MXenes have captured the leadership position among lightweight shielding materials due to many advantages, including their excellent shielding performance, outstanding metallic conductivity, low density, large specific surface area, tunable surface chemistry, and solution processability. MXenes triggered a huge interest in the materials research community, leading to over 100 reported publications on MXenes' EMI shielding within 3 years. Many MXenes composites and hybrids in different structural forms, such as compact and laminate structures, layer‐by‐layer assemblies, porous foams and aerogels, and segregated structures, have been explored to further improve the intrinsic EMI shielding properties of MXenes. This article comprehensively reviews the recent advancements in MXene‐based EMI shielding materials with different structural morphologies and provides an insight into future challenges and guidelines for finding material solutions for the next‐generation shielding applications. Abstract : MXenes with various structural forms have become the flag‐bearer candidates to combat detrimental electromagnetic interference. This review on MXenes yields a comprehensive insight into the present findings, future challenges, and possible solutions for electromagnetic shielding.